2016
DOI: 10.3892/ol.2016.5250
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-221/222 by a microRNA sponge promotes apoptosis in oral squamous cell carcinoma cells through upregulation of PTEN

Abstract: MicroRNA-221 and microRNA-222 (miR-221/222) have been identified as oncogenes and confirmed to be overexpressed in various types of cancer. However, the regulation mechanism of miR-221/222 in oral squamous cell carcinoma (OSCC) remains to be fully elucidated. Previously, an miR-221/222 sponge was successfully constructed and its effect on the downregulation of miR-221/222 expression was investigated. In the present study, the dual luciferase reporter assay revealed a phosphatase and tensin homolog (PTEN) delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…In addition, a large number of valuable epidemiological studies have shown that UGT1A7 affects individuals' susceptibility to various cancers, such as pancreatic cancer [36],gastrointestinal carcinomas [37].Now our study suggests that miR-221- [38,39,40,41,42], a control the progression of the tumors. For example, miR-221-3p has be regarded as a tumor biomarker that can be used to assess the clinical prognosis of breast cancer [15]. In healthy humans, it has been shown that miR-221-3p plays a role in the process of vascular proliferation, while the tumor promoter, miR-221-3p regulates the apoptosis of tumor cells.…”
Section: The Prospective Target Genes Of Mir-221 In Hnsccmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a large number of valuable epidemiological studies have shown that UGT1A7 affects individuals' susceptibility to various cancers, such as pancreatic cancer [36],gastrointestinal carcinomas [37].Now our study suggests that miR-221- [38,39,40,41,42], a control the progression of the tumors. For example, miR-221-3p has be regarded as a tumor biomarker that can be used to assess the clinical prognosis of breast cancer [15]. In healthy humans, it has been shown that miR-221-3p plays a role in the process of vascular proliferation, while the tumor promoter, miR-221-3p regulates the apoptosis of tumor cells.…”
Section: The Prospective Target Genes Of Mir-221 In Hnsccmentioning
confidence: 99%
“…Recent years have seen an increasing concentration of research in, microRNA (miRNA) [10,11], which are a type of highly conserved single-stranded non-coding RNA, containing 17~22 nucleotides and are involved in the process of tumorigenesis, cell survival, and chemosensitivity [12,13,14]. They bind the 3'non-region (3'UTR) of different target mRNA (messenger RNA) genes to degrade or inhibit the mRNA translation of target genes associated with a tumor suppressor function [13,15,16]. In normal healthy individuals, miR-221-3p is observed to play a role in the process of vascular proliferation [17], while the tumor promoter, microRNA-221 is involved in the process of regulation of apoptosis of the tumor cell [18,19,20] and is associated with a variety of cancer types, including hepatocellular cancer [21], cutaneous melanoma [19], prostate cancer [20],non-small cell lung cancer [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Благодаря присутствию в их последовательности нуклеотидов участков посадки микроРНК, ýти молекулы способны выступать в роли так называемой молекулярной губки, принимающей на себя атаку микроРНК и тем самым снимающей блок с настоящей матричной РНК [46]. При помощи такой «губки» было достигнуто почти полное удаление из клетки активных miR-221/222, что повлекло за собой усиление апоптоза клеток плоскоклеточного рака ротовой полости [47].…”
Section: пути направленной регуляции экспрессии геновunclassified
“…These findings suggest the potential role of plasmatic miRNAs in oral carcinogenesis, as well as their high diagnostic value for early oral cancer detection. MiR-221/miR-222 cluster has been shown to promote oral carcinogenesis by downregulation of PTEN [46]. As in oral cancer, upregulated circulating miR-222 levels have been observed in a wide variety of tumors, e.g., pancreatic cancer [47] and glioma [48].…”
Section: Plasma and Serummentioning
confidence: 99%